Prince Caspian - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline; HarperCollins Children's Books (London : HarperCollins Children's Books, 1998)
Four children help Prince Caspian and his army of Talking Beasts to free Narnia from evil.
Keywords: Narnia (Imaginary place) -- Fiction; Fantastic fiction